Dilated optic nerve sheath by ultrasound predicts mortality among patients with acute intracerebral hemorrhage - Francisco Antunes Dias; Maria Clara Zanon Zotin; Frederico Fernandes Alessio-Alves; Rui Kleber do Vale Martins Filho; Clara Monteiro Antunes Barreira; Otavio Costa Vincenzi; Paula Muñoz Venturelli; Gregoire Boulouis; Joshua Norkin Goldstein; Octavio Marques Pontes-Neto (Arquivos de Neuro-Psiquiatria)
Background Intracerebral hemorrhage (ICH) is a deadly disease and increased intracranial pressure (ICP) is associated with worse outcomes in this context.